Study of usefulness of rotary tiller in agricultural practice - Mohd Hudzari, Razali; Rizuwan, Yahaya; Abdul Ssomad, M.Abd Halim; Syazili, Roslan (2013)
The purpose for this paper is to know the uses of physical rotary implement and the procedure on how to handle it about engage and disengage with 3-point hitch of tractor. Estimation on basic calculation of diesel fuel consumption by the tractor is calculated and found that with depth of tilling on 1cm and rpm of 1700, 48 seconds is needed to complete the tilling of the given length. From the data, the number of piston revolution and fuel consumption for 48 seconds is 1359.84 revolution and 0.0024 litres. Thus, the amount of fuel consumed is 1.765 times 10-6 litres per revolution. This paper showed the hand on knowledge and information about the method for handling the tractor and the rotary implement while the basic knowledge the uses of the rotary implement in agriculture is briefly discussed.